2016
DOI: 10.1007/s00467-016-3449-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intrarenal renin–angiotensin system in the progression of renal disease

Abstract: The intrarenal renin-angiotensin system (RAS) has many well-documented pathophysiologic functions in both blood pressure regulation and renal disease development. Angiotensin II (Ang II) is the major bioactive product of the RAS. It induces inflammation, renal cell growth, mitogenesis, apoptosis, migration, and differentiation. In addition, Ang II regulates the gene expression of bioactive substances and activates multiple intracellular signaling pathways that are involved in renal damage. Activation of the An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 81 publications
2
44
0
1
Order By: Relevance
“…Ang II, as the strongest effector molecule in the RAS system, was reported to be involved in the pathogenesis of various kidney diseases through inducing renal inflammation [22, 23]. Recent evidence demonstrated that the NLRP3 inflammasome played a detrimental role in kidney diseases [24-26].…”
Section: Discussionmentioning
confidence: 99%
“…Ang II, as the strongest effector molecule in the RAS system, was reported to be involved in the pathogenesis of various kidney diseases through inducing renal inflammation [22, 23]. Recent evidence demonstrated that the NLRP3 inflammasome played a detrimental role in kidney diseases [24-26].…”
Section: Discussionmentioning
confidence: 99%
“…1 Proximal tubular AGT concentrations range from 300–600 n m in anesthetized rats, which greatly exceeds the concentrations of free Ang I and Ang II in tubular fluid. 3 Given the molecular size (50–60 kDa) of AGT, it seems unlikely that significant amounts of plasma AGT filters across the glomerular membrane, further supporting the concept that proximal tubular cells secrete AGT directly into the tubules. 3 To determine whether circulating AGT is a source of urinary AGT, Nakano et al 11 examined the glomerular permeability of AGT by multi-photon imaging, and found an extremely low glomerular permeability of injected exogenous AGT.…”
mentioning
confidence: 93%
“…Their efficacy suggests that factors other than angiotensin II (Ang II) are involved in renal disease progression. 3 While evidence suggests that local RAS in various tissues, including the brain, heart and vasculature are regulated independently of the systemic RAS, 1 most current research focuses on analyzing the role of tissue RAS in the kidneys. 4 …”
mentioning
confidence: 99%
See 2 more Smart Citations